2022
DOI: 10.3390/horticulturae8100920
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Provides Insights into Anthocyanin Accumulation in Mulberry Fruits

Abstract: Mulberry fruits are rich in anthocyanins, which are important secondary metabolites that give mulberries their bright color, favorable taste and high nutritional quality, making them a popular fruit. However, few studies have focused on the molecular mechanism underlying anthocyanin accumulation in mulberries and the gene regulatory networks of anthocyanin biosynthetic pathways remain largely unknown. In this study, we performed RNA sequencing to identify differentially expressed genes (DEGs) associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Interestingly, the fruit coloration of 'XJ-BS' is mainly in the peel (Figure S2b), while other cultivars are colored throughout the fruit (Figures 8b,e and S3b). In this study, the anthocyanins are abundant in purple or black mulberry fruits but not in white fruits, the differences in the levels and proportions of anthocyanins result the differently colored mulberry fruits (white, purplish red, purple and black) (Figures 8 and S1-S3), as reported in previous studies [53][54][55][56].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, the fruit coloration of 'XJ-BS' is mainly in the peel (Figure S2b), while other cultivars are colored throughout the fruit (Figures 8b,e and S3b). In this study, the anthocyanins are abundant in purple or black mulberry fruits but not in white fruits, the differences in the levels and proportions of anthocyanins result the differently colored mulberry fruits (white, purplish red, purple and black) (Figures 8 and S1-S3), as reported in previous studies [53][54][55][56].…”
Section: Discussionsupporting
confidence: 84%
“…Anthocyanins are essential for physiological and biochemical activities of plant developments, including antioxidant, protection against plant damage, attraction of animals for pollination and seed dispersal (Guo et al 2011). Mulberry fruits are rich in anthocyanins, which are important secondary metabolites that give mulberries their vibrant color, favorable taste and high nutritional quality, and play an important role in protecting human health (Mo et al 2022). Reportedly, anthocyanins (cyanidin-3-O-glucoside and cyanidin-3rutinoside) are minor components in immature mulberry fruit but accumulate over the course of maturation (Oki et al 2006).…”
Section: Flavonoids Of Mulberry Fruit At Different Developmental Stagesmentioning
confidence: 99%
“…A combined transcriptomic and proteomic approach was used to study the molecular mechanism underlying the mulberry (Morus atropurpurea) fruit response to Ciboria carunculoides infection to develop mulberry varieties with resistance to fungal pathogens (Dai et al 2019). Transcriptomic techniques were used to reveal the gene regulatory network of the anthocyanin biosynthesis pathway during mulberry fruit development (Mo et al 2022); moreover, it has been shown that the downregulation of avanone 3-hydroxylase (F 3 H) during mulberry fruit development and maturation can result in a decrease in the anthocyanin content and a subtle increase in the iso avonoid content (Dai et al 2022). The comprehensive metabolic pro le of mulberry fruit at various maturation stages, including the levels of fatty acids and anthocyanins, was investigated by gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC)-based metabolic pro ling (Lee et al 2016).…”
Section: Introductionmentioning
confidence: 99%